PENGARUH KEBIJAKAN DALAM PENGGUNAAN DANA BERDASARKAN SUMBER PENDANAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bahria Bahria (Jurnal Bisnis dan Kewirausahaan, 2019)
The aims of the research are (1) the influence short-term funds use policy for short-term needs to profitability ; (2) the influence short-term funds use policy for long-term needs to profitability; (3) the influence long-term funds use policy for long-term needs to profitability; (4) the influence long-term funds use policy for short-term needs to profitability;(5) the influence of fund use policy based on funding sources simultaneously to profitability. The research use secondaray data through a financial statement especially balance sheet & profit and loss from 31 december 2011 up to 31 december 2017. the data analyze with linear regression for spss 22 program. The Result of this research show that : the short-term funds use policy for short-term needs positive influece to profitability ; (2) the short-term funds use policy for long-term needs positive influece to profitability; (3) the influence long-term funds use policy for long-term needs negative influece to profitability; (4) the long-term funds use policy for short-term needs positive influece to profitability;(5) the fund of use policy based on funding sources simultaneously positive influece to profitability.